Service-learning as a tool for global citizenship. Creating synergies between social labor centers and university - Cid-Romero, Esperanza; Blasco-Serrano, Ana Cristina; Dieste-Gracia, Belén; Arranz-Martínez, Pilar (Iberoamerican Journal of Development Studies, 2025)
The Service-Learning (SL) methodological strategy enables professional competences and values of civic responsibility, critical thinking and social transformation to be addressed, that promote the development of global citizenship. Within this framework, an evaluative research study on the implementation of ApS in the Municipal Network of Socio-Labour Centres of Zaragoza is presented. The aim of this work is to evaluate the implementation process of this pedagogical strategy, and how its development affects the teaching-learning process, as well as the development of global citizenship values. A mixed methodology is used, with questionnaires, participant observation and focus groups. The results show the need for good planning and organisation for an adequate implementation of actions in the local or global context and in collaboration with other social agents. After the implementation, an improvement of personal and professional competences and the development of Global Citizenship values are perceived.
Keywords: global citizenship education; vocational competences; employment training; service-learning